Development an open source web based marine spatial information system - Hazim Mohamad Madani, 1991-, author; Abdullah Omar, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2014